STUDI RUGI DAYA SISTEM KELISTRIKAN BALI AKIBAT PERUBAHAN KAPASITAS PEMBANGKITAN DI PESANGGARAN - Pramana, I P. A. Edi; Ariastina, W. G.; Sukerayasa, I. W. (Jurnal Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i02p08, 2015)
In the years of 2014 until 2015 Pesangaran plant capacity undergo changes due to the expiration of employment contract lease diesel units and also the addition of new plant unit of 200 MW PLTMG. An increase or reduction in plant capacity of electrical system Bali will lead to significant changes to the load flow, power losses and energy losses in the circuit of Bali electrical Transmission system. Load flow analysis and power losses in Bali electricity system is simulated in five scenarios. Scenario 1 for the conditions of existing in 2014, scenario 2 is currently experiencing a reduction Pesanggaran plant capacity in December 2014, scenario 3 is currently experiencing Pesanggaran plant capacity additions in 2015 by using a peak load of 2014, scenario 4 is the scenario 3 with using predicted peak load in 2015, and scenario 5 is the scenario 4 with assuming the Celukan Bawang plant operates at 130 MW. Based on the results obtained by analysis, scenario 2 has the most power and energy loss about 46.34 MW and 300.39 GWh. For the loss of power and energy Bali electrical systems after Pesanggaran plants changes in 2015 are 38.57 MW and 250.05 GWh.
Keywords: Pembangkit, aliran daya, skenario, susut daya, susut energi.